Optimalisasi Upaya Pemberantasan Korupsi di Kabupaten Nabire - Zaid, muhammad; Bauw, Lily (JURNAL EKOLOGI BIROKRASI, 2024)
This article discusses the issue of corruption as a social crime that negatively impacts the development of Nabire Regency in Papua. The article aims to identify the causes of widespread corruption in the region and proposes strategies to combat it. The research for this article is based on a literature review, using scientific sources such as journal articles, monographs, and reference books, as well as information from the media and secondary data from corruption cases in the region. The slot thailand analysis of the data reveals that corruption is driven by factors such as a luxurious lifestyle, lack of financial control, opportunities for corruption, weak supervision, and the high costs of regional head elections,. To optimize efforts to eradicate corruption, the article recommends increasing integrity, promoting an anti-corruption culture, strengthening law enforcement, implementing policy instruments, enhancing inter-agency cooperation, and encouraging public participation in reporting corruption.